Deforestation pattern dynamics in protected areas of the Brazilian Legal Amazon using remote sensing data - Cabral, Ana I.R.; Saito, Carlos; Pereira, Henrique; Laques, Anne Elisabeth (Applied geography (Sevenoaks), 2018)
Forest fragmentation and deforestation are subjects of great concern in tropical regions, namely in South America and Africa, contributing to a rapid loss of tropical forest area and with serious implications for ecosystem functioning and biodiversity conservation. Despite the decrease in deforestation rates in recent years, the Brazilian Amazon, with the largest continuous region of tropical forest in the world, has suffered the greatest recorded losses, which have been contributing to continuous habitat fragmentation and a reduction in the territory occupied by Amerindian populations. In an attempt to preserve the remaining habitats and forests, Brazil has been adopting land conservation policies, including the implementation of protected areas. Protected areas (PAs) possess the potential to significantly reduce habitat fragmentation by conserving large, contiguous areas of land. In order to examine how effective PAs are at conserving forest area in the Brazilian Legal Amazon, patterns of deforestation are analyzed and compared, inside and outside the PAs, through landscape metrics calculated using the Patch Analyst and V-LATE extensions of a Geographic Information System. Two different sources (the Hansen Global Forest Change Dataset and the Brazilian National Institute for Space Research's (INPE) PRODES project) of annual forest cover-loss data derived from satellite imagery at medium-to-high spatial and temporal resolutions are compared at two-yearly intervals across 2002–2016. Additionally, fragmentation levels associated with deforestation patterns are assessed through an index modeled using a set of uncorrelated landscape metrics, and the associated change factors and trend are discussed. Results show that there is greater fragmentation in some PAs located in Mato Grosso and Pará States, especially those near the “arc of deforestation”, and that Yanomami Indigenous Lands (YIL) are tending towards more fragmentation. Although some PAs are in a critical condition, findings show they all actively contribute to improved conservation of the native ecosystem and, in conjunction with sustainable management policies, will continue to help reduce or avoid forest fragmentation and degradation processes. •Forest fragmentation and deforestation resulted from land use changes in tropical regions.•Brazil, and in particular the Brazilian Legal Amazon, suffered from high rates of forest loss for decades.•Protected Areas (PAs) protect forests and preserve the territories of the Amerindian populations while reduce deforestation.•Deforestation pattern analysis inside and outside PAs using derived remote-sensing data.•Modelling a fragmentation index using landscape metrics to evaluate fragmentation level in PAs.